Thermal conductivity computations of sintered hollow sphere structures - Veyhl, Christoph (MDPI, 2012)
The thermal conductivity of sintered hollow sphere structures (HSS) is investigated within the scope of this paper. For this purpose, finite element analyses based on micro-computed tomography images are performed on HSS structures. The complex geometry of the real sintered HSS sample is accurately captured with this new hybrid method. The numerical computations are investigated in three perpendicular directions (i.e., x, y and z) in order to examine the anisotropic material behaviour. The results indicate that sintered HSS reveals quasi-isotropic behaviour in terms of effective thermal conductivity. For the first time, the influence of the sphere wall thickness of real HSS is investigated. To this end, the computed tomography data is carefully manipulated by changing the thickness of the hollow sphere wall. The variation of the wall thickness alters the relative density and has a significant influence on the thermal conductivity. The influence of the relative density on the thermal conductivity reveals a linear dependency.